Peptide-Based Biomaterials for Bone and Cartilage Regeneration - Kausik Kapat; Sakshi Kumbhakarn; Rahul Sable; Prashil Gondane; Shruti Takle; Pritiprasanna Maity (Biomedicines, 2024)
The healing of osteochondral defects (OCDs) that result from injury, osteochondritis, or osteoarthritis and bear lesions in the cartilage and bone, pain, and loss of joint function in middle- and old-age individuals presents challenges to clinical practitioners because of non-regenerative cartilage and the limitations of current therapies. Bioactive peptide-based osteochondral (OC) tissue regeneration is becoming more popular because it does not have the immunogenicity, misfolding, or denaturation problems associated with original proteins. Periodically, reviews are published on the regeneration of bone and cartilage separately; however, none of them addressed the simultaneous healing of these tissues in the complicated heterogeneous environment of the osteochondral (OC) interface. As regulators of cell adhesion, proliferation, differentiation, angiogenesis, immunomodulation, and antibacterial activity, potential therapeutic strategies for OCDs utilizing bone and cartilage-specific peptides should be examined and investigated. The main goal of this review was to study how they contribute to the healing of OCDs, either alone or in conjunction with other peptides and biomaterials.